2021
DOI: 10.3390/diagnostics11112104
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound for Precise Sentinel Lymph Node Biopsy in Women with Early Breast Cancer: A Preliminary Study

Abstract: Background: Sentinel lymph node biopsy (SLNB), as a common method for axillary staging of early breast cancer, has gradually attracted people’s attention to the false-negative rate and postoperative complications. The aim of the study is to investigate the clinical value of preoperative contrast-enhanced ultrasound (CEUS) for intraoperative SLNB in early breast cancer patients. Methods: A total of 201 patients scheduled for SLNB from September 2018 to April 2021 were collected consecutively. Preoperative CEUS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
4
3
0
Order By: Relevance
“…However, it has been demonstrated that preoperative knowledge of the drainage route of the SLC is critical for successful SLNB. 18,20 Drainage patterns of SLC were summarized in our study: In all patients included, we found 4 drainage patterns and 5 drainage subtypes, of which single SLN-single SLC was the most common, which is consistent with the previous study. 20,21 The results of Luo et al provide a more detailed summary of the drainage patterns of SLC, and they classified it into 11 LDPS and 31 subtypes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, it has been demonstrated that preoperative knowledge of the drainage route of the SLC is critical for successful SLNB. 18,20 Drainage patterns of SLC were summarized in our study: In all patients included, we found 4 drainage patterns and 5 drainage subtypes, of which single SLN-single SLC was the most common, which is consistent with the previous study. 20,21 The results of Luo et al provide a more detailed summary of the drainage patterns of SLC, and they classified it into 11 LDPS and 31 subtypes.…”
Section: Discussionsupporting
confidence: 91%
“…18,20 Drainage patterns of SLC were summarized in our study: In all patients included, we found 4 drainage patterns and 5 drainage subtypes, of which single SLN-single SLC was the most common, which is consistent with the previous study. 20,21 The results of Luo et al provide a more detailed summary of the drainage patterns of SLC, and they classified it into 11 LDPS and 31 subtypes. 22 PCEUS combined with body surface markers showed SLN and LC more visually on the skin surface.…”
Section: Discussionsupporting
confidence: 91%
“…Our study shows that CEUS is a feasible preoperative localization method for SLN, with a detection rate of 95.7% (88/92). However, consistent with other studies, the average number of SLNs per patient identified by CEUS (1.23) was significantly less than that of SLNs identified by MB/ICG (2.63) (19,20). This finding may be related to the inherent properties of commonly used intraoperative SLN tracers, such as MB.…”
Section: Discussionsupporting
confidence: 88%
“…First, a lowfrequency linear probe (3-9 MHz) was used for all ultrasound examinations. Although this probe provides the best SLN visualization on the Philips iU22 scanner (18,19), a higher resolution ultrasound probe could further improve the reliability of our results when initially recruiting patients using B-mode ultrasound. Second, the surface markers were used in the CEUS identification SLN procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation